STUDIES ON CYCLICAL LIPID CHANGES IN THE OVARY OF RASBORA DANICONIUS - C. P. OMBASE,; R. D. BODARE, (The Bioscan, 2012)
In present study the cyclical changes of lipids in the ovary of Rasbora daniconius were carried out. The neutral lipid and phospholipids were studied during the four stages of breeding cycle. It was found that neutral lipids were accumulated in the ovary during pre breeding stage and metabolized during active breeding period i.e. lipids get decreased during breeding stage. Again it was found that lipids get accumulated from post breeding stage and subsequent period of quiescence. The phospholipids slowly increased from pre breeding period and attained high concentration during the active breeding period. Such increase in phospholipid values correlates with increasing number of ovum. The phospholipids showed the decreasing trend from post breeding period followed by quiescent period.